Hating Adolescents Test (HAT): a preliminary development of a measure to assess hating among adolescents - Pace, Ugo (Psychiatr Psychol Law, 2020)
The phenomenon of haters is becoming common among adolescents. The aims of the present research were to evaluate the preliminary psychometric properties of the Hating Adolescents Test (HAT), an ad hoc questionnaire created to evaluate online and offline hate (Study 1), and possible risk factors connected with hate (Study 2). Participants (202 female and 200 male) of this study completed the HAT, the How I Think Questionnaire, the Buss–Perry Aggression Questionnaire, and the Penn State Worry Questionnaire. Descriptive statistics were calculated, and exploratory factor analysis and confirmatory factor analysis were applied. Preliminary data suggest how males reported higher level of hate than females. Cronbach’s alpha coefficient suggested excellent reliability of the measure. Results of this study also revealed satisfactory construct, convergent and divergent validity. Moreover, the results show a significant gender difference on the variables of the study (pathological worry and hostility aggressiveness). The mediation model suggests how hostile aggressiveness mediated the relationship between pathological worry and hate. HAT is a brief self-report questionnaire composed of 12 items scored on a 5-point Likert scale, with good psychometric properties.